Host Susceptibility Modulates Escovopsis Pathogenic Potential in the Fungiculture of Higher Attine Ants - Jiménez-Gómez, Irina; Barcoto, Mariana O.; Montoya, Quimi V.; Goes, Aryel C.; Monteiro, Lana S. V. E.; Bueno, Odair C.; Rodrigues, Andre (Frontiers in Microbiology, 2021)
Health and disease emerge from intricate interactions between genotypes, phenotypes, and environmental features. The outcomes of such interactions are context-dependent, existing as a dynamic continuum ranging from benefits to damage. In host-microbial interactions, both the host and environmental conditions modulate the pathogenic potential of a microorganism. Microbial interactions are the core of the agricultural systems of ants in the subtribe Attina, which cultivate basidiomycete fungi for food. The fungiculture environment harbors a diverse microbial community, including fungi in the genus Escovopsis that has been studied as damage-causing agent. Here, we consider the ant colony as a host and investigate to what extent its health impacts the dynamics and outcomes of host-Escovopsis interactions. We found that different ant fungal cultivars vary in susceptibility to the same Escovopsis strains in plate-assays interactions. In subcolony-Escovopsis interactions, while healthy gardens gradually recover from infection with different concentrations of Escovopsis conidia, insecticide-treated fungus gardens evidenced traits of infection and died within seven days. The opportunistic nature of Escovopsis infections indicates that diseases in attine fungiculture are a consequence of host susceptibility, rather than the effect of a single microbial agent. By addressing the host susceptibility as a major modulator of Escovopsis pathogenesis, our findings expand the understanding of disease dynamics within attine colonies.